الأناركيَّة في التصور الإسلامي: The Concept of Anarchism in Islam - Al-Shamari نايف بن نهار (الدراسات الإسلامية, 2023)
This article studies one of the famous modern political theories, that is, anarchism. This theory denies the necessity of political authority in society, based on the notion that the existence of political authority would rob the independence and freedom of individuals, which are more important than political authority itself. The theory was advocated by prominent philosophers of different ideologies, such as William Godwin (d. 1836), Pierre-Joseph Proudhon (d. 1865), Mikhail Alexandrovich Bakunin (d. 1876), and Pyotr Alexeyevich Kropotkin (d. 1921). The paper begins by analyzing the concept of anarchism and then discusses the term chosen by the Arab translators of anarchist philosophy, on which the anarchists depend to reject the idea of political authority and base their argument. Finally, the study concludes with a discussion of the Islamic position on the issue of dealing with power, to clarify the difference between the Islamic and anarchist concepts. The research relied on the analytical method of discussing and analyzing the texts of anarchist theorists, as well as analyzing the Islamic contents related to the issue.